MEMANFAATKAN KAEDAH KONTRASTIF DALAM PENYELIDIKAN ISLAM - Awang, Idris (Jurnal Syariah, 2019)
Contrastive Analysis (CA) is a research method widely used in Applied Linguistics to provide guidlines to course planners and terachers in contructing suitable foreign language courses to learners of a common linguistic background. Despite the debate on the practicality of its contrastive analysis hypothesis, CA has contributed tremendously to foreign language teaching and learning. If that’s the case in Linguistics, c ould CA do the same thing to other areas of studies? The current article looks into the possibilty in the Islamic Studies, particular the Islamic law, by looking into researches in the area.